Eksplorasi Sharia Compliance dan Transparansi Sistem Akuntansi pada Koperasi Syariah di Kota Makassar - Ambarwati Akib; Nurul Chalisa Majiding; Dwi Utami (Program Studi Akutansi - Universitas Nusa Putra, 2025)
This study aims to evaluate the implementation of sharia compliance and the transparency of the accounting system at KSPPS Bakti Huria Syariah. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observation, and document analysis. The results indicate that KSPPS Bakti Huria has implemented a PSAK Syariah-based accounting system supported by automated digital tools. The cooperative employs mudharabah, murabahah, ijarah, and wadiah contracts in its operations. Sharia compliance is maintained through the supervision of the Sharia Supervisory Board (DPS), and financial reporting meets sharia accounting principles, although members' understanding of the reports remains limited. The study recommends enhancing members' sharia literacy, continuous staff training, and strengthening the DPS’s role in disseminating financial information to improve the overall quality of sharia principles implementation.